Understanding the law - Carper, Donald L.; Mietus, Norbert J. (South-Western Cengage Learning, 2012)
A text that discusses how various aspects of the law affect the individual, filling a void for those looking for a more introductory text that covers many of the personal law issues that confront people in their everyday lives. It uses hypothetical and real examples to illustrate important points of the law and to inspire lively class discussion.